1992
DOI: 10.1002/jat.2550120109
|View full text |Cite
|
Sign up to set email alerts
|

Review of chemical and uv light‐induced melanomas in experimental animals in relation to human melanoma incidence

Abstract: In a few epidemiological studies on oil refinery workers, a slight excess of melanoma incidence has been reported. To see if this might be linked to exposure to polycyclic aromatic hydrocarbons (PAHs) contained in refinery streams, a review of animal data on the relationship between PAH exposure, UV light and melanoma induction has been carried out and compared with human data. This revealed that the highly carcinogenic PAH 7,12-dimethylbenz[a]anthracene (DMBA) was capable of inducing melanomas in hamsters, mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Possible mechanisms for an effect of PAHs, in particular DMBA, on cutaneous melanoma are as follows: (i) PAHs act as a competitive inhibitor of the enzyme tyrosinase, which is responsible for melanin synthesis; and/or (ii) PAHs lead to the generation of superoxide radicals in the presence of UVR, causing DNA cleavage 74 . Laboratory experiments with DMBA can induce melanoma in both mice and hamsters, 75 and its effects are exacerbated by sunlight 76 . Benzene toxicity may be related to the formation of its metabolites: hydroquinone, phenols, and catechols.…”
Section: Discussionmentioning
confidence: 99%
“…Possible mechanisms for an effect of PAHs, in particular DMBA, on cutaneous melanoma are as follows: (i) PAHs act as a competitive inhibitor of the enzyme tyrosinase, which is responsible for melanin synthesis; and/or (ii) PAHs lead to the generation of superoxide radicals in the presence of UVR, causing DNA cleavage 74 . Laboratory experiments with DMBA can induce melanoma in both mice and hamsters, 75 and its effects are exacerbated by sunlight 76 . Benzene toxicity may be related to the formation of its metabolites: hydroquinone, phenols, and catechols.…”
Section: Discussionmentioning
confidence: 99%
“…Later experiments showed that a single skin application of DMBA followed by prolonged (6-12 months) application of croton oil is the most efficient method for melanoma induction, resulting in development of melanomas in 15-20% of treated mice (Berkelhammer and Oxenhandler, 1987;Shapiro et al, 1996). In contrast to DMBA, other carcinogenic polycyclic aromatic hydrocarbons were inefficient at melanoma production (Ingram, 1992). The precise mechanisms and genetic basis of melanoma formation in mice and humans remain mostly unclear.…”
mentioning
confidence: 99%
“…The experiment got satisfactory outcome for skin melanoma in rats, hamsters, and Guinea pigs, but only when DMBA and UVR-B were applied in high doses, disregarding the relationship of refinery workers exposure with high incidence of melanoma, because researchers found that the workers were exposed only a small fraction of thishydrocarbon 24 . Yang 25 reports high toxicity of polycyclic aromatic hydrocarbons in fuels human skin.…”
Section: Comparing Macroscopic and Microscopic Resultsmentioning
confidence: 99%